Artikel Laporan KKN 6A1 Kelompok 5 Desa Srimukti RT 01/RW 02 - Anggun Rika Mandasari; Alvanesya Pramudita; Annisa Suci Wulandari; Cristiana Vicensia Aritonang; Dea Wahyuni; Dzaki Rafi Fauzan; Endang Hutabarat; Ery Teguh Prasetyo; Hadita; Muhammad Asyharul Fata; Nila Khairani; Riska Yuliana; Rizky Edi Nurdiansyah; Silvia Nursafitri (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2023)
There is still a lack of public understanding and knowledge regarding UMKM management in a business and the importance of increasing children's interest in reading, some people do not understand the dangers of waste for the surrounding environment if littering will have an impact on the environment. How to use waste by recycling it to increase economic income. Based on this, the Community Service Program (KKN) activities seek to bridge the increase in knowledge about the importance of UMKM and foster an interest in reading from an early age in children's. Srimukti Village is one of the places in North Tambun sub-district which is one of the places to support the quality of the community in RT 01/RW 02 Srimukti village. To reduce economic problems and tackle waste so that flooding does not occur and it is important that we motivate children to read. Therefore we have a program to provide education and increase interest in reading for children in RT 01/RW 02 Desa Srimukti. Indicators of successful implementation of this KKN work program are: suitability of work program plans and implementation, level of community and children's participation in each activity, and increasing public knowledge regarding UMKM, utilizing waste waste which will increase economic income and understanding the importance of reading interest from an early age in Srimukti Village. Some of the outputs generated through community service KKN activities in Srimukti Village, namely: providing guidance and implementation on how to manage UMKM in a business to the community, socializing the benefits of waste waste to increase economic income, and providing guidance and increasing the potential of children's in the interest read early. Keywords: UMKM, The Interest Read, Economic Income, KKN